Corporate social and environmental responsibilities in the Arctic Zone of the Russian Federation: theoretical and methodological approaches - Bobylev, Nikolai; Gadal, Sébastien; Sergunin, Alexander; Tynkkynen, Veli-Pekka (Корпоративное управление и инновационное развитие экономики Севера, 2021)
International audience The main research objective of this study is to examine various theoretical approaches to understanding the nature of corporate social and environmental responsibility in the Arctic Zone of the Russian Federation (AZRF), as well as the motivation of businesses to make commitments in this area. Methodologically, the study is based on the structural-functional and discursive approaches that allow us to reveal the internal features of the Russian and foreign discourses on the social and environmental responsibility of business in the Russian Arctic. The scientific contribution of this study is that as a result of the work carried out, it reveals the specificity of theories that treat corporate social and environmental responsibility as a form of social partnership or a way of sharing benefits (economic sociology); the behaviour of corporations as “good citizens” of society (sociology and political science); part of the strategy of corporate risk management and competitiveness (corporate management) and/or sustainable development (economic planning, ecology, state and municipal management, social work). Another scientific contribution of this study is that identifies three groups of motives that drive big business in the case of taking on social and environmental obligations in the AZRF: the desire of companies to increase their attractiveness as business partners, to justify the legitimacy of their economic activities in the region and to take into account the so-called political costs in order to reduce the likelihood of the state introducing uncomfortable rules and regulations for companies. The results obtained can be used in the activities of business units responsible for the social and environmental policy of companies in the Russian Arctic, as well as regional and municipal authorities regulating the activities of large industrial and extractive companies in the Far North. Основная исследовательская задача данного исследования заключается в изучении различных теоретических подходов ...